The impact of mineral fertilisers on the physicochemical properties of soil in maize cultivation - A. Khavkhun (Рослинництво та ґрунтознавство, 2024)
The use of mineral fertilisers is a critical factor in modern agriculture, significantly influencing the physicochemical properties of soil, which in turn affects crop yield and quality. Understanding these impacts is essential for sustainable agricultural practices. This study aimed to determine the effects of different types and quantities of mineral fertilisers on the physicochemical properties of soil in the context of maize cultivation. The research involved experimental field trials with varying applications of mineral fertilisers. Soil samples were collected at different stages of maize growth and analysed for parameters such as pH, electrical conductivity, organic matter content, and nutrient availability (nitrogen, phosphorus, potassium). The study employed a range of methods to investigate the effects of mineral fertilisers on soil properties, including soil preparation, application of various types and doses of fertilisers, maize planting, plant growth monitoring, and analysis of soil physicochemical characteristics. The application of mineral fertilisers led to significant changes in soil pH, with some fertilisers causing acidification and others increasing alkalinity. Fertilised plots showed increased electrical conductivity, indicating a rise in soluble salt content. Variations in organic matter content were observed, dependent on the type and dosage of fertilisers used. It was determined that fertilised plots exhibited elevated levels of nitrogen, phosphorus, and potassium, directly correlating with the type and quantity of fertiliser applied. The highest maize yield was achieved with balanced applications of nitrogen-phosphorus-potassium (NPK) fertilisers, underscoring the importance of balanced nutrient management. These findings provide valuable insights for optimising fertiliser use, which may contribute to improved soil health, increased maize yield, and sustainable agricultural practices